Evaluation of some laboratory data in traumatic dogs - Semih Altan; Fahrettin Alkan; Yılmaz Koç (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study is to determine prognosis and prevent potential complications in blood samples taken from stray dogs brought into the surgery clinic with complaints of trauma based on hematology, blood gas, serum biochemistry and oxidative stress levels. Materials and Methods: The study was conducted on 15 traumatized stray dogs and 9 healthy dogs. The obtained blood samples were analyzed for hematology, blood gas, serum biochemistry [alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatine kinase (CK), Phosphorus (P), cholesterol (Chol), creatinine (Crea), gamma glutamyl transferase (GGT), lactate dehydrogenase (LDH), total protein (TP), triglyceride (Trig), blood urea nitrogen (BUN)] and thiobarbutyric acid reactive substance (TBARs) values. Results: ALP, AST, CK, P, Crea and TBARs levels were different in traumatized dogs compared to healthy dogs (p˂0.05). Lactate and monocyte values were higher, while potassium and ionized calcium values were lower compared to reference values of dogs in blood gas and hematologic values. Conclusion: As a result, the biochemical profile varies depending on the extent of trauma in traumatized dogs, whereas high levels of oxidative stress related to the severity of trauma in dogs with no other underlying disease can be considered as a biological marker. However, in order to determine the prognosis and prevent the complications, further studies are needed to establish more specific markers.